2017
DOI: 10.11646/phytotaxa.295.1.1
|View full text |Cite
|
Sign up to set email alerts
|

USING Next-Generation Sequencing (NGS) TO UNCOVER DIVERSITY OF WOOD-DECAYING FUNGI IN NEOTROPICAL ATLANTIC FORESTS

Abstract: A targeted amplicon-based metagenomics approach (metabarcoding) provides detailed access to the diversity of the mycobiome in any substrate in distinct environments on Earth. Fungi are the main decomposers of lignocellulosic woody debris in terrestrial forested ecosystems, contributing significantly to the global carbon cycle. The main objectives of this study were to assess the fungal taxonomic diversity in fallen woody debris samples from two Neotropical forest fragments (rainforest and seasonal forest), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Ascomycota were dominant, particularly in wood of the 1 st decay class where their frequency increased to over 89% of all fungi detected. Dominance of Ascomycota in deadwood was also observed by Vaz et al (2017). Many Ascomycota taxa detected were soft rot fungi, meaning that they can break down cellulose and hemi-cellulose, but not harder structural substances such as lignin (Mäkelä et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Ascomycota were dominant, particularly in wood of the 1 st decay class where their frequency increased to over 89% of all fungi detected. Dominance of Ascomycota in deadwood was also observed by Vaz et al (2017). Many Ascomycota taxa detected were soft rot fungi, meaning that they can break down cellulose and hemi-cellulose, but not harder structural substances such as lignin (Mäkelä et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…In the six 3-30-year-old Q. petraea logs there were 264 307 different OTUs, which is 127-fold more than the 2 080 OTUs found in nine samples of 3-year-old Q. rubra logs using high-throughput sequencing (by van der Wal et al, 2017), but less than the 687 662 and 1 861 279 OTUs found in 20 samples of broadleaved trees from two locations in neotropical Atlantic forests using massively parallel sequencing (Vaz et al, 2017). There were also 277 fungal taxa, which is more than the 141 taxa detected in deadwood of Quercus robur L. using the classical method based on isolation and microscopic analysis (Kwaśna et al, 2016b), the 100 taxa detected in neotropical Atlantic forests (Vaz et al, 2017), and the 15 species detected in Q. rubra logs (by van der Wal et al, 2017). In two other tree species, beech and Scots pine, respectively 96 and 138 fungal taxa were detected by isolation and microscopic analysis (Fukasawa et al, 2009;Kwaśna et al, 2016b).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Yet, despite these factors being well documented, after more than a decade of use there is no clear consensus as to what extent metabarcoding is quantitative. Many studies report their findings in a quantitative manner where the relative read abundance (RRA) (Deagle et al, 2018) is interpreted as the relative abundance of biomass (Kowalczyk et al, 2011;Soininen et al, 2015;Sousa et al, 2016;Vaz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, methodological biases, limitations of the markers and bioinformatic analysis, may lead to misleading conclusions (Lindahl et al 2013, Vaz et al 2017. Operational taxonomic units are based on sequences with ≥ 97% similarity.…”
Section: Comparison Between Culture-dependent and Culture-independentmentioning
confidence: 99%